Uptake of the Hepatitis B Vaccine Among Pre‐Service Health Professionals in Rwanda - Bivegete Kenny Ntwari; Felix K. Rubuga; Silene Jolie Uwingabiye; Vincent Dushimimana; Jean Baptiste Hategekimana; Serieux Cyubahiro; Ivan Steve Rwema; Daniel Ukwishatse; Patrick Karakwende; Jean Muhire; Adolphe Ndikubwimana; Theoneste Ntakirutimana; et al. (Public Health Challenges)
ABSTRACT Background High hepatitis B vaccine uptake has led to significant reductions in hepatitis B infection rates and associated health burdens in many countries. Despite the administration of the same vaccine, there has been a lack of emphasis on pre‐service health professionals. This study aimed at assessing uptake of hepatitis B vaccine among pre‐service health professionals at the University of Rwanda. Methods This was a cross‐sectional descriptive study. Data were collected using a self‐administered questionnaire, whereas data analysis was performed using SPSS (Version 25; IBM Corp). Results A total of 360 respondents participated in the study; among them, 218 (60.6%) were males. About half of the participants, 170 (47.2%), scored between 40% and 60% on the knowledge assessment, whereas the majority of the respondents, 354 (98.3%), were aware of the hepatitis B vaccine. Most of the participants 334 (92.8%), were vaccinated, whereas 231 (69.2%) received the complete 3‐dose vaccination. The most commonly cited reason for not getting vaccinated was lack of awareness (45%). The factors that influenced vaccination status were free vaccination provided by institutions, awareness of the vaccine, and knowledge of hepatitis B infection and its vaccine. Conclusion Pre‐service health professionals are at risk of hepatitis infection due to low coverage of hepatitis B vaccination and lack of comprehensive knowledge and awareness regarding the hepatitis B infection and its vaccination.